1999
DOI: 10.1046/j.1432-1327.1999.00507.x
|View full text |Cite
|
Sign up to set email alerts
|

Deregulation of the signaling pathways controlling urokinase production

Abstract: We review the evidence in support of the notion that, upon experimental oncogenic transformation or in spontaneous human cancers, mitogenesis and expression of urokinase (uPA) and its receptor (uPAR) are activated through common signaling complexes and pathways. It is well documented that uPA, uPAR or metalloproteinases (MMPs) are overexpressed in tumor cells of mesenchymal or epithelial origin and these molecules are required for tumor invasion and metastasis. Furthermore, oncogenic stimuli, which may render … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
86
0

Year Published

2001
2001
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(89 citation statements)
references
References 104 publications
3
86
0
Order By: Relevance
“…In addition, binding of uPA to its receptor can stimulate epithelial cell motility by a mechanism that is independent of proteolysis (Juan et al, 2001). uPA expression can be regulated by growth factors that bind to tyrosine kinase receptors and this activates the Ras signaling pathway (Aguirre-Guiso et al, 1999). This pathway involves the activation of MAPK by c-Raf, which in turn activates the extracellular signal regulated kinase (ERK).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, binding of uPA to its receptor can stimulate epithelial cell motility by a mechanism that is independent of proteolysis (Juan et al, 2001). uPA expression can be regulated by growth factors that bind to tyrosine kinase receptors and this activates the Ras signaling pathway (Aguirre-Guiso et al, 1999). This pathway involves the activation of MAPK by c-Raf, which in turn activates the extracellular signal regulated kinase (ERK).…”
Section: Discussionmentioning
confidence: 99%
“…The role of MAPKs in regulation of MMP-9 and uPA expressions in malignant cells has been well understood. At least two (extracellular signalregulated kinase and c-Jun NH 2 -terminal kinase/stress-activated protein kinase) of the three so-called mitogenic pathways known so far in mammalian cells induce up-regulation of MMP-9 and uPA (41,42). Recently it has been shown that inhibition of p38 leads to reduced MMP-9 expression and invasion by tumor cells (43), and p38 stabilizes uPA mRNA and invasiveness in MDA-MB-231 cells (44).…”
Section: Figmentioning
confidence: 99%
“…This step is involved in both tumor invasion and the initial step of angiogenesis (see reviews; Aguirre-Ghiso et al, 1999a;Blasi, 1993). This protease itself has serine protease activity and also acts as an upstream regulator of plasmin and matrix metalloproteases (MMPs).…”
Section: Introductionmentioning
confidence: 99%